Tecido hepático e corpo adiposo de rã-touro (Lithobates catesbeianus) submetido a diferentes fotoperíodos - Maia Pereira, Marcelo; Ribeiro Filho, Oswaldo Pinto; Reis Troni, Allan; Takamura, Angela Emi; Menegasso Mansano, Cleber Fernando; Barros Nascimento, Fernando; Camargo Filho, Claudio Barberini (My University, 2011)
The study was conducted to evaluate the liver tissue weight, body fat weight, the fatty somatic index and the liver somatic index of bullfrogs subjected to three photoperiod during the growing phase (initial 30 days) and finishing (60 days). The treatments were 16 h light and 8 h dark, 12 h of light and dark and 8 h light and 16 h dark. The experimental design was completely randomized design with three replications. We used 36 bullfrogs/m2 weighing from 22 to 28 g. The results were submitted to ANOVA and Tukey Test at 5% probability. Differences were found for the weight of body fat, liver tissue weight, liver somatic index and fatty somatic index the bullfrog to the treatments and the study periods and there is greater accumulation of energy to ninety days. The photoperiod did not influence body weight and fat weight of the liver tissue of bullfrog at the end of the fattening period and the difference fatty somatic index and liver somatic index were influenced by body weight of animals.
Liver tissue and body fat of bullfrog (Lithobates catesbeianus) under different photoperiod